Simultaneous multislice MRI thermometry with a single coil using incoherent blipped‐controlled aliasing. Issue 2 (11th August 2019) - Quah, Kristin; Poorman, Megan E.; Allen, Steven P.; Grissom, William A.
Abstract : Purpose: To increase volume coverage in real‐time MR thermometry for transcranial MR‐guided focused ultrasound (tcMRgFUS) ablation, without multiple receive coils. Theory and Methods: Multiband excitation and incoherent blipped‐controlled aliasing were implemented in a 2DFT pulse sequence used clinically for tcMRgFUS, and an extended k‐space hybrid reconstruction was developed that recovers slice‐separated temperature maps assuming that heating is focal, given slice‐separated pretreatment images. Simulations were performed to characterize slice leakage, the number of slices that can be simultaneously imaged with low‐temperature error, and robustness across random slice‐phase k‐space permutations. In vivo experiments were performed using a single receive coil without heating to measure temperature precision, and gel phantom FUS experiments were performed to test the method with heating and with a water bath. Results: Simulations showed that with large hot spots and identical magnitude images on each slice, up to three slices can be simultaneously imaged with less than 1 ∘ C temperature root‐mean‐square error. They also showed that hot spots do not alias coherently between slices, and that an average 86% of random slice‐phase k‐space permutations yielded less than 1 ∘ C temperature error. Temperature precision was not degraded compared to single‐slice imaging in the in vivo SMS scans, and the gel phantom SMS temperature maps closely tracked single‐slice temperature in the hot spot, with no coherent aliasing to other slices. Conclusions: Incoherent controlled aliasing SMS enables accurate reconstruction of focal heating maps from two or three slices simultaneously, using a single receive coil and a sparsity‐promoting temperature reconstruction.